13C NMR investigations and molecular order of nematogens with biphenyl and bithiophene at terminus. Issue 10 (9th August 2021) - Boopathi, A. A.; Bhavani, T.; Lobo, Nitin P.; Narasimhaswamy, T.
ABSTRACT: Four rod-like mesogens in which biphenyl and bithiophene units are located at one terminus are synthesised and the occurrence of enantiotropic nematic phase is established by hot-stage optical polarising microscopy and differential scanning calorimetry. For biphenyl based mesogens (BP-1 and BP-2), the mesophase is observed irrespective of number of phenyl rings in the amine moiety. For bithiophene (BT-1), on the other hand, the mesophase is only noted when the amine component has two rings. The mesophase range for BP-1 is found to be 163.7 ◦ C and for BT-1 and BP-2, the values are 84.7 ◦ C and 11.1 ◦ C, respectively. BP-1 and BT-1 are subjected to 13 C NMR investigation in nematic phase to determine the local order and accordingly, oriented 1D 13 C and 2D SAMPI-4 NMR experiments are accomplished. The remarkable feature of the SAMPI-4 spectrum of BP-1 measured at 145 ◦ C in nematic phase is observation of the 13 C- 1 H dipolar coupling value of 16.67 kHz for terminal carbon (C18). For BT-1, however, the dipolar coupling value for C18 is found to be 8.60 kHz in nematic phase (138 ◦ C). Such large values of 13 C- 1 H dipolar couplings for the terminal ring carbons of the nematogens offer orientation of the rings of the core unit directly. Graphical Abstract: uf0001